Culm anatomy of Bouteloua and relatives (Gramineae: Chloridoideae: Boutelouinae) - Siqueiros-Delgado, Ma. Elena (Instituto de Ecología, A.C., 2007)
Transverse sections of mature flowering culms of Boutelouinae were analyzed to explore the usefulness of the culm anatomy to assess phylogenetic relationships. Fifty-five taxa were surveyed from the field and greenhouse collections. Although leaf anatomy in Boutelouinae has been shown to possess systematic utility, culm anatomy has been very little explored. In the Boutelouinae, only few traits of the culm middle internodal region with phylogenetic value, were found. Kranz structures (cells and radial chlorenchyma), number and position of the vascular bundles, and sclerenchyma girders are some culm anatomy characters that can be useful for inferring relationships at higher levels (family, tribes, genera). Culm anatomy suggests close relationships between B. eriopoda and B. eriostachya, and between B. ramosa and B. breviseta, and supports the inclusion of the satellite genera into Bouteloua. The Kranz structures and chloroplast shape appear to be the most variable features of this region of the culm.